2019
DOI: 10.1089/zeb.2018.1703
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Object Discrimination in Zebrafish: Behavioral Performance and Scopolamine-Induced Cognitive Deficits at Different Retention Intervals

Abstract: The object discrimination test allows the testing of different memory retention periods. However, few behavioral endpoints have been measured in fish species such that retention is often assessed using a single parameter (time spent in object area). Here, we aimed to explore the object discrimination test in zebrafish by assessing their behavioral performance after 1 h or 24 h retention interval periods. To characterize putative interaction-like behaviors, fish were tested in the absence or presence of scopola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…According to Figure 6B, all three doses of LS, but especially the doses of 1 mg/L and 3 mg/L, significantly reversed the recognition memory impairment caused by the SCOP administration (p < 0.01), increasing zebrafish preference for the new object. Because scopolamine changes transitions to the object areas, locomotion, and anxiety-related responses, the interaction-like behaviors described here may predictably reflect a distinct behavioral performance associated with an object, which has been described by other authors [29,30]. However, the exact significance of such behaviors, as well as the neurochemical mechanisms involved in these responses, still require further scrutiny.…”
Section: Spatial Memory In Y-maze Impact On Anxiety-like Behavior In Ntt and Nor Testssupporting
confidence: 59%
See 1 more Smart Citation
“…According to Figure 6B, all three doses of LS, but especially the doses of 1 mg/L and 3 mg/L, significantly reversed the recognition memory impairment caused by the SCOP administration (p < 0.01), increasing zebrafish preference for the new object. Because scopolamine changes transitions to the object areas, locomotion, and anxiety-related responses, the interaction-like behaviors described here may predictably reflect a distinct behavioral performance associated with an object, which has been described by other authors [29,30]. However, the exact significance of such behaviors, as well as the neurochemical mechanisms involved in these responses, still require further scrutiny.…”
Section: Spatial Memory In Y-maze Impact On Anxiety-like Behavior In Ntt and Nor Testssupporting
confidence: 59%
“…The NOR test evaluates the short-and long-term memory of the fish. The test is based on the ability to recognize an unfamiliar object when placed in its area [30]. The parameter that was estimated in this test conducted by our research group focused on highlighting the preference regarding the newly identified object of the zebrafish taken in the study.…”
Section: Spatial Memory In Y-maze Impact On Anxiety-like Behavior In Ntt and Nor Testsmentioning
confidence: 99%
“…To explore whether baicalein 5,6-dimethyl ether treatment affects locomotion or anxiety-like behavior, the animals were submitted to NTT, according to a previously described method by Levin et al [ 58 ]. NTT is widely used to measure exploratory behavior and novelty stress habituation [ 59 ]. Zebrafish ( n = 10 per group) were individually introduced in the apparatus filled with 1.5 L of home tank water and their behaviors were recorded for 6 min.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the object discrimination test measures the ability of a zebrafish to retain a memory (Figure 1). Zebrafish are introduced to a novel object to test whether they are still able to recognize the object after 1-or 24-h post-introduction (Stefanello et al, 2019). One study revealed that the zebrafish telencephalon and thalamus are the major brain regions that are involved in processing visual discrimination (Messina et al, 2020).…”
Section: Zebrafish Model In Behavioral Neurosciencementioning
confidence: 99%